Estimation Of Maximum Ground Acceleration Value Based On Mentawai Earthquake Scenario Using Atkinson Boore and Zhao - Khairunnissa, Shafira; Syafriani; Fauzi, Ahmad; Zulhendra, Zulhendra (Mataram University, 2024)
We have estimated the value and intensity of maximum ground acceleration in West Sumatra based on the Mentawai earthquake scenario by using the formulation of Atkinson Boore (2003) and Zhao (2006). This study aims to determine the PGA value of an area as the level of activity and intensity of the earthquake in West Sumatra region from the Mentawai earthquake scenario as a measure of damage caused by the earthquake and analyze its distribution. This study uses earthquake information data for the period 1900-2023 with magnitude > 7 SR and depth < 100 km and shear wave velocity model at a depth of 30 meters (Vs 30) sourced from the National Earthquakes Information Center US Geological Survey (NEIC/USGS) catalog. After that, calculations are carried out so that the estimated maximum ground acceleration value is obtained using the Atkinson Boore (2003) and Zhao (2006) formulas. The maximum ground acceleration and earthquake intensity values for each city/regency in West Sumatra were calculated with a 0.1Â° grid. The estimation results show that the largest values for each scenario are in Mentawai Islands and South Pesisir because those areas are close to the subduction zone. In addition, it is also influenced by the epicenter, magnitude and soil type in the region. So that the maximum ground acceleration value in West Sumatra ranges from 0.007 g - 2.117 g with earthquake intensity ranging from I - X+ MMI. This indicates that the area is vulnerable to damage if an earthquake occurs. Keywords: Earthquakes, Atkinson Boore, Zhao, PGA, Intensity